Clinical Efficacy and Accuracy of 3D‐Printed Medical Devices: A Systematic Review and Meta‐Analysis - Vishnu Priya Veeraraghavan; Krishna Mohan Surapaneni; Seyed Ali Mosaddad (Health Science Reports, 2026)
ABSTRACT Aim This systematic review aimed to assess the clinical and experimental utility of three‐dimensional (3D) printing in medical and dental applications, with a focus on its impact on surgical precision, procedural efficiency, and patient‐centered results. Methods A systematic review and meta‐analysis were conducted following PRISMA 2020 guidelines. Database searches identified 481 records, of which 15 studies were included in the review; eight contributed to one or more meta‐analyses. Quantitative analysis assessed operative time and intraoperative blood loss using mean differences with random‐effects models. Study quality was evaluated using NOS, Cochrane RoB 2, and ROBINS‐I tools. Results Fifteen studies were included; eight contributed to at least one meta‐analysis. At the study level, 5 of 7 comparative studies (71.4%) favored 3D printing for accuracy, fit, alignment, or planning; all 10 studies reporting procedural or operative time favored it; and 4 of 7 (57.1%) reported better patient‐centered or functional outcomes. Random‐effects models showed no statistically significant reduction in operative time (MD, −24.88 min; 95% CI, −62.45 to 12.70; p = 0.19; I 2 = 100%) and significantly lower intraoperative blood loss (MD, −61.55 mL; 95% CI, −82.62 to −40.49; p < 0.001; I 2 = 83%). Conclusions Available evidence suggests that 3D printing may improve procedural precision, patient‐specific planning, and selected clinical outcomes; however, extreme heterogeneity and limited outcome‐specific evidence preclude broad generalization.